Analisis Studi Longitudinal Fenomena Kemiskinan Pasca Pandemi Covid-19 Perspektif Ekonomi Digital - Hasbiah Hasbiah; Deni Anggreani Sutomo; Nur Imam Saifuloh; Emily Nur Saidy (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The Covid-19 pandemic has changed the social and economic landscape around the world, increasing poverty levels and economic uncertainty. In this context, this study adopts a longitudinal approach and a digital economy perspective to analyze the post-pandemic poverty phenomenon. With a focus on Surabaya City, East Java, this study identifies poverty trends, patterns of access to and use of digital technology, and their impact on people's income and welfare. The results show significant fluctuations in poverty levels, with digital technology playing a role in increasing income and access to health and education services. Correlation analysis confirms a negative relationship between the use of digital technology and poverty rates. The findings highlight the importance of investment in technology infrastructure, digital literacy training, and digital inclusion policies to ensure the benefits of digital technology are equitably distributed across society. In conclusion, this study illustrates the important role of digital technology in addressing post-pandemic poverty, providing important insights for public policy and community development practice.